Ferroptosis in idiopathic pulmonary fibrosis: mechanisms, impact, and therapeutic opportunities - Yao, Mingjun; Liu, Zheng; Zhao, Wei; Song, Siyuan; Huang, Xiaobo; Wang, Yi (Frontiers in Immunology, 2025)
Idiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease characterized by progressive scarring, alveolar destruction, and limited therapeutic options. Although the exact etiology of IPF remains unclear, emerging evidence suggests that ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxidation and oxidative stress, plays a significant role in its pathogenesis. Ferroptotic stress not only compromises alveolar epithelial cell integrity, but also triggers inflammatory responses and profibrotic signaling cascades that activate and sustain fibroblast dysfunction. This review delineates the core regulatory pathways of ferroptosis, iron metabolism, lipid peroxidation, antioxidant defenses, mitochondrial remodeling, and RNA editing, with an emphasis on their relevance in IPF. We explore how epithelial injury and macrophage-derived signals initiate ferroptosis, and how fibroblast subsets, shaped by scRNA-seq-defined heterogeneity and plasticity, respond to these cues by reinforcing ECM deposition and oxidative stress. Therapeutic avenues targeting ferroptosis, including antioxidant supplementation, iron chelation, and modulation of lipid metabolism, are discussed alongside cell-specific interventions and nanodelivery strategies. By integrating recent advances in molecular profiling and ferroptosis biology, this review provides a framework for leveraging ferroptosis as a tractable target in IPF and identifies novel directions for precision antifibrotic therapy.